VD_FINDINFO HC / 2019 / 306 vom 25. April 2019 - VD Tribunal cantonal (2019)
AUTORITÉ PARENTALE, DIVORCE, RELATIONS PERSONNELLES, OBLIGATION D'ENTRETIEN, PRÉVOYANCE PROFESSIONNELLE | 122 CC, 124b al. 2 CC, 273 CC, 296 al. 2 CC, 298 CC, 298 CPC (CH), 308 al. 1 let. a CPC (CH)